Temperature-Dependent Properties of Graphene on SiC Substrates for Triboelectric Nanogenerators - Wang, Sen; Wan, Lingyu; Li, Ding; Chen, Xiufang; Xu, Xiangang; Feng, Zhe Chuan; Ferguson, Ian T. (Frontiers in Materials, 2022)
Graphene has excellent properties such as ultra-high electrical conductivity, high carrier mobility, and thermal conductivity, with a promising application in the field of triboelectric nanogenerators (TENGs). We present a systemic investigation to explore structural, optical, and temperature-dependent properties of single- and bi-layer graphene on SiC substrates, prepared by the decomposition of SiC and transferred substrate methods and their applications in TENGs. Compared to the transferred graphene onto a SiC substrate, graphene grown by the decomposition of SiC has a better crystalline quality and surface morphology, fewer impurities, and a more stress effect between graphene and the substrate. It also exhibited a longer correlation length of Raman phonons, implying better crystalline perfection. With the increase in temperature, the phonon correlation length, L, increases synchronously with TENG outputs. Among them, the TENG with a bi-layer graphene grown by the decomposition of SiC showed the best performance, especially at high temperatures. These studies provide an essential reference for further applications of graphene on SiC substrates in TENG-based devices.